2022
DOI: 10.3389/fcimb.2022.979091
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional BST2/tetherin against HIV-1, other viruses and LINE-1

Abstract: Bone marrow stromal cell antigen 2 (BST2), also known as CD317, HM1.24, or tetherin, is a type II transmembrane glycoprotein. Its expression is induced by IFN-I, and it initiates host immune responses by directly trapping enveloped HIV-1 particles onto the cell surface. This antagonistic mechanism toward the virus is attributable to the unique structure of BST2. In addition to its antiviral activity, BST2 restricts retrotransposon LINE-1 through a distinct mechanism. As counteractive measures, different viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…In summary, the genes up-regulated in their expression encode the pro-inflammatory cytokine IL-6, which can be induced by the presence of viruses, MX1 (MX dynamin-like GTPase 1), MX2 (MX dynamin-like GTPase 2), IFI6 (interferon alpha inducible protein 6) and ISG15 (interferon-stimulated gene 15), which inhibit viral replication, OAS2 (2’-5’-oligoadenylate synthetase 2) and OAS3 (2’-5’-oligoadenylate synthetase 3), which synthesize secondary messengers that serve to activate RNase L, which degrades viral and cellular RNA, and ISG20 (interferon stimulated exonuclease gene 20 kDa), which is an endoribonuclease that supports the degradation of viral RNA (Tanaka et al, 2014), (Sun et al, 2012; Haller et al, 2015; Zhu et al, 2015; Sajid et al, 2021; Deymier et al, 2022). In addition, the genes BST2 (bone marrow stroma cell antigen 2), IFI27 (interferon alpha-inducible protein 27), DDIT4 (DNA-damage-inducible transcript 4), GBP4 (guanylate binding protein 4), DDX60 (DEAD-box helicase 60), which are also involved in the antiviral immune response, are up-regulated (Miyashita et al, 2011; Tretina et al, 2019; Busse et al, 2020; Ullah et al, 2021; Zhao et al, 2022). It was shown that a type I interferon (IFN) response occurs during P. berghei replication in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the genes up-regulated in their expression encode the pro-inflammatory cytokine IL-6, which can be induced by the presence of viruses, MX1 (MX dynamin-like GTPase 1), MX2 (MX dynamin-like GTPase 2), IFI6 (interferon alpha inducible protein 6) and ISG15 (interferon-stimulated gene 15), which inhibit viral replication, OAS2 (2’-5’-oligoadenylate synthetase 2) and OAS3 (2’-5’-oligoadenylate synthetase 3), which synthesize secondary messengers that serve to activate RNase L, which degrades viral and cellular RNA, and ISG20 (interferon stimulated exonuclease gene 20 kDa), which is an endoribonuclease that supports the degradation of viral RNA (Tanaka et al, 2014), (Sun et al, 2012; Haller et al, 2015; Zhu et al, 2015; Sajid et al, 2021; Deymier et al, 2022). In addition, the genes BST2 (bone marrow stroma cell antigen 2), IFI27 (interferon alpha-inducible protein 27), DDIT4 (DNA-damage-inducible transcript 4), GBP4 (guanylate binding protein 4), DDX60 (DEAD-box helicase 60), which are also involved in the antiviral immune response, are up-regulated (Miyashita et al, 2011; Tretina et al, 2019; Busse et al, 2020; Ullah et al, 2021; Zhao et al, 2022). It was shown that a type I interferon (IFN) response occurs during P. berghei replication in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…BST2 can also function as an immunomodulatory molecule. For example, Toll‐like receptors (TLRs) or other pattern recognition receptors (PRRs) recognized the endocytic compartments containing BST2 and trapped HIV‐1 virions, indirectly inducing IFN‐I responses in infected primary cells 47 . Here, the interaction of BST2 and HBx may also regulate the JAK/STAT pathway after HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…BST2 (bone marrow stromal cell antigen 2), also known as CD317, is a type of transmembrane glycoprotein involved in virus reproduction suppression and immune regulation [ 66 ]. Using the hTERT immortalized human bone marrow MSC colonies, it has been demonstrated that the MSCs from the CD317 + colony have increased cell areas and up-regulated mRNA levels of immunosuppressive genes than the CD317 − MSCs in vitro [ 67 ].…”
Section: St Generation Of Msc Markersmentioning
confidence: 99%